THE FACTORS ASSOCIATED WITH HEALTH WORKERS IN INTERPERSONAL COMMUNICATION SATISFACTIONS OF OUTPATIENT HEALTH CENTER PANDAN TAPANULI DISTRICT MIDDLE OF 2014 working area pandan KEC. PANDAN 2014 - danelta hutagaol; Lita Sri Andayani; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Factors associated with interpersonal communication, namely, openness, empathy, being supportive, positive attitude, and equality will have an impact on patient satisfaction is a measure to assess the quality of health service in primary health care. This study aimed to analyze the factors associated with health workers in interpersonal communication satisfaction of outpatient health center pandan Tapanuli district middle of 2014. The study design wass cross sectional study, the population of this study are a number of citizens of pandan and used  samples totaling 98 people. Results respondents (55.1%) does not pick satisfied on interpersonal communication on patient health workers in health centers to get service there is a relationship of openness (p=50% ), empaty (p=52%), being supportive (p=46%) , attitude positive (p=42,9%). Expected health workers who work in puskesmas pandan Tapanuli district centered to improve interpersonal communication to improve patient satisfaction scores in order to create good communication .